MAKNA LEKSIKAL DAN MAKNA GRAMATIKAL JUDUL BERITA PORTAL KOMPAS.COM EDISI OKTOBER 2024 - Ayu Yulianti; Yunengsih; Dodi Firmansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to analyze the lexical and grammatical meaning in the news headlines of the October 2024 edition of Kompas.com. The method in this research is descriptive qualitative, with data collection techniques, namely library techniques and data analysis techniques, namely content analysis techniques. The aim of this research is to find the lexical and grammatical meaning of the October 2024 edition of the Kompas.com news title, analyze the lexical and grammatical meaning of the October 2024 edition of the Kompas.com news title, explain the meaning of the news that has been analyzed, and find words whose meanings give rise to errors in meaning. The procedures carried out in this research include: 1) Determining the theme, 2) Searching for information, 3) Collecting research data, 4) Presenting the data, and 5) Compiling research results. The technique used is a data analysis technique, using content analysis methods to obtain logical references that can be researched further. The results of the analysis obtained in this research contain the lexical and grammatical meaning of the October edition of the Kompas.com news title. The meaning analysis study proves that we can know the importance of the truth of information in the news title so as to minimize errors in interpreting the title of information in the news and avoid misunderstanding the meaning of the information.